2014
DOI: 10.3329/dujbs.v23i1.19820
|View full text |Cite
|
Sign up to set email alerts
|

Effects of waste water irrigation on the growth and nutrient status of kalmi (Ipomoea aquatica Forssk.)

Abstract: A pot experiment was carried out to observe the effect of waste water irrigation on the growth and nutrient status of Kalmi (Ipomoea aquatica) in the nethouse of the Department of Soil, Water and Environment, University of Dhaka. The soil samples were collected from Tejgaon, Rampura, Sitalakhya and from the north?side of Rampura area, the latter is located at a distance from the polluted area and has been used as the control soil. The pots containing the first three soil samples were irrigated with wastewater … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…A vegetable (Kalmi: Ipomoea aquatic ) was grown in that soil and adjacent Sitalakhya river water was used as irrigation water (Pot experiment). After harvest (growing time: 35 days), the concentration of Zn, Cu, Pb and Cd were 113.16, 36.69, 14.07 and 0.08 mg/kg [ 200 ]. Soils contain higher concentrations of metals due to sediment deposition and irrigation with contaminated river water [ 201 , 202 ].…”
Section: Changes Of Heavy Metals Concentration In Soilmentioning
confidence: 99%
See 2 more Smart Citations
“…A vegetable (Kalmi: Ipomoea aquatic ) was grown in that soil and adjacent Sitalakhya river water was used as irrigation water (Pot experiment). After harvest (growing time: 35 days), the concentration of Zn, Cu, Pb and Cd were 113.16, 36.69, 14.07 and 0.08 mg/kg [ 200 ]. Soils contain higher concentrations of metals due to sediment deposition and irrigation with contaminated river water [ 201 , 202 ].…”
Section: Changes Of Heavy Metals Concentration In Soilmentioning
confidence: 99%
“…After harvest (growing time: 35 days), the concentration of Zn, Cu, Pb and Cd were 113.16, 36.69, 14.07 and 0.08 mg/kg [ 200 ]. Soils contain higher concentrations of metals due to sediment deposition and irrigation with contaminated river water [ 201 , 202 ]. Several researchers analyzed soil from area adjacent to river and compared with uncontaminated soil and found that these soils contain higher concentrations of heavy metals [ 12 , 182 ].…”
Section: Changes Of Heavy Metals Concentration In Soilmentioning
confidence: 99%
See 1 more Smart Citation